Judicial Review on Health Emergency Law: The Challenge to Judicial Independence of Indonesian Constitutional Court - Radian Salman; Rosa Ristawati; Bernard Nicholas Singarimbun (Jurnal Wawasan Yuridika, 2025)
Emergency laws are often enacted by the President to address urgent situations and safeguard public welfare. Still, it risks fundamental rights and the rule of law without proper scrutiny.  This research is addressed to analyse the tendency of judicial independence of the Constitutional Court in conducting a review over a Government Regulation in Lieu of Law (Perppu), especially based on Court Decision Number 138/PUU-VII/2009. This article is important because it addresses the critical issue of judicial independence in the context of emergency laws, which can have significant implications for fundamental rights and the rule of law. This research is a doctrinal research  with focus on analyzing constitutional and statutory provisions, legal principles, case law and also comparative approach. Subsequently, data collection techniques were employed utilizing a document study, then analyze qualitatively. The findings of this research is that the enactment of emergency law turns into a double challenge for judges to decide the case, particularly when the judges are appointed by the President. Moreover, judicial review on emergency law shows the more tension between executive power and judicial oversight compared to  judicial review of legislation. This helps deepen the understanding of how courts balance constitutional principles during emergencies and provides valuable insights for other jurisdictions facing similar challenges.